Investigation of anti-BSA IgE production post-vaccination in healthy, reactor and commercial plasma donor horses - Perry, Elizabeth (Kansas State University, 2020)
Background: There is anecdotal evidence to suggest risk associated with the administration of commercial plasma to neonatal foals that have previously ingested commercial powdered colostral supplementation within the first 24 hours of life. Bovine serum albumin (BSA) is present in both commercial powdered colostral supplements and commercial equine vaccines. Previous studies in human and equine medicine have investigated the immune response to non-viral vaccine antigens, including BSA and have documented the presence of anti-BSA IgE following vaccination. Objectives: To measure anti-BSA immunoglobulin E (IgE) levels post-vaccination in healthy horses, those experiencing vaccine reactions and those utilized for commercial plasma harvesting. Methods: Serum was collected from 65 healthy horses at day 0, 14, 28, 90, 180, 270 and 365 after vaccination as well as from 26 horses at day 1, 180 or 270 after vaccination that had developed an adverse vaccine reaction. Serum was collected from 4 horses that had never been vaccinated and 10 horses that were part of a commercial plasma donation herd. Anti-BSA IgE concentrations were evaluated by enzyme-linked immunosorbent assay (ELISA). Results: Anti-BSA IgE levels were not detected in non-vaccinated horses and were present in all vaccinated horses. Younger horses demonstrated a higher fold change in post-vaccination anti-BSA IgE levels compared to older horses. Across all age groups there was not a significant difference between pre- and post-vaccine anti-BSA IgE levels in healthy horses. There was not a significant difference in anti-BSA IgE levels between commercial plasma donor horses and healthy horses. There was not a significant difference in post-vaccination anti-BSA IgE levels between reactor horses and healthy horses at day 180 and 270 post-vaccination. Main Limitations: There was a small number of reactor horses at day 180 and 270 post-vaccination with most samples being at 24 hours post-vaccination. There were no healthy horse samples available for 24 hours after vaccination; therefore, it was not possible to compare the two groups at this time point. The vaccination history of the commercial plasma donor horses was unknown.
Keywords: Equine; BSA; Adverse plasma reactions; Vaccines